1994
DOI: 10.1136/jcp.47.11.1010
|View full text |Cite
|
Sign up to set email alerts
|

Which proliferation markers for routine immunohistology? A comparison of five antibodies.

Abstract: For routine use, MIB1 or polyclonal Ki67 are the best proliferation markers in conventional histological preparations. The other markers tested cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
7

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 38 publications
4
55
0
7
Order By: Relevance
“…MIB-1 is a monoclonal antibody recognizing Ki-67 nuclear nonhistone protein expressed throughout the mitotic cycle, with the exception of the G 0 phase. Immunostaining with MIB-1 or polyclonal anti-Ki-67 antibodies yields the same results (17). In normal vulvar skin and vulvar/cervical mucosa, MIB-1 positivity is found exclusively in the parabasal nuclei of the squamous epithelium (3, 5, 18 -22).…”
Section: Discussionsupporting
confidence: 62%
“…MIB-1 is a monoclonal antibody recognizing Ki-67 nuclear nonhistone protein expressed throughout the mitotic cycle, with the exception of the G 0 phase. Immunostaining with MIB-1 or polyclonal anti-Ki-67 antibodies yields the same results (17). In normal vulvar skin and vulvar/cervical mucosa, MIB-1 positivity is found exclusively in the parabasal nuclei of the squamous epithelium (3, 5, 18 -22).…”
Section: Discussionsupporting
confidence: 62%
“…Rose et al found a qualitatively similar immune staining using MIB-1 and polyclonal Ki-67 antibodies, but quantitative comparisons were not performed. 23 To our knowledge, the only previous study that has presented relevant quantitative data is the study of Torp in 1997. 47 He determined Ki-67 LIs in 11 glioblastomas by staining with the prototypic Ki-67 antibody in addition to the same four Ki-67 equivalent antibodies that were used in our Table 2 Ki-67 labelling indices in tonsillar squamous epithelium from 10 cases stained with four different Ki-67 equivalent antibodies study.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of the Ki-67 proliferative tumor marker as assessed by the MIB-1 antibody is well established in several types of tumors, e.g., squamous cell carcinoma of the esophagus, non-Hodgkin's lymphoma, non-small cell lung cancer, cervical cancer, pancreatic head cancer, prostatic cancer (7,(25)(26)(27)(28)(29), as well as by Delahunt in Wilms' tumor (11). In the present study, a prognostic value of proliferative activity of the blastemal, i.e., blastemal MIB-1 expression was found for clinical progression and tumor-specific survival.…”
Section: Discussionmentioning
confidence: 99%